Estimated Water Savings Potential of Florida-Friendly Landscaping Activities - Mackenzie J. Boyer; Michael D. Dukes (EDIS)
To help homeowners predict the impact of implementing some of the water conservation measures listed on the Florida-Friendly Landscaping™ checklist, this fact sheet offers a table of estimated water savings. Homeowners can select activities which are the best fit for their landscape and can also see which have the most conservation potential. The water savings is compared to a baseline case of typical irrigation behavior. This 6-page fact sheet was written by Mackenzie Boyer and Michael Dukes, and published by the UF Department of Agricultural and Biological Engineering, August 2015. (Photo credit: Michael Gutierrez, UF/IFAS)